IMPROVEMENT OF CUSTOMS CONTROL FORMS IS THE KEY TO SIMPLIFICATION OF CUSTOMS PROCEDURES - Abdunor Suyunov; Rushana Fakhriddinova (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the reforms carried out in the Republic of Uzbekistan in the field of customs affairs, reveals the essence of customs control carried out in relation to goods and vehicles crossing the customs border, the forms of customs control used, the specifics of applying the risk management system based on the recommendations of the World Customs Organization, in the implementation of customs control and customs clearance, the study of recommendations of the Kyoto Convention "On Simplification and Harmonization of Customs Procedures", analysis of the experience of developed countries in the customs clearance of goods in the Republic of Uzbekistan.